2022
DOI: 10.1002/celc.202101449
|View full text |Cite
|
Sign up to set email alerts
|

Charge Storage Behaviour of α‐MoO3 in Aqueous Electrolytes – Effect of Charge Density of Electrolyte Cations

Abstract: In this paper, we show that the electrochemical performance of α-MoO 3 electrode is significantly dependent on the charge density of three studied aqueous electrolyte cations, i. e. Na + , Mg 2 + and Al 3 + . The charge storage capacity of the α-MoO 3 electrode increases with increasing cation charge density. On the other hand, the initial coulombic efficiency decreases, and the charge transport kinetics are slowed with increasing charge density. This study provides an insightful understanding of the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The apparent diffusion coefficient of Al 3+ ions estimated using the Warburg coefficient from modeling was found to be 1.9·10 −14 and 3.9·10 −15 cm 2 s −1 for the MoO 3 _(011)&(102) and MoO 3 _(00k) electrodes, respectively. Notably, different diffusion coefficients were determined for electrodeposited MoO 3 , depending on the size and charge of the cation; for instance, D Na+ was higher than D Al 3+ 36 . Moreover, the values of D Al 3+ are in good agreement with values presented here.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent diffusion coefficient of Al 3+ ions estimated using the Warburg coefficient from modeling was found to be 1.9·10 −14 and 3.9·10 −15 cm 2 s −1 for the MoO 3 _(011)&(102) and MoO 3 _(00k) electrodes, respectively. Notably, different diffusion coefficients were determined for electrodeposited MoO 3 , depending on the size and charge of the cation; for instance, D Na+ was higher than D Al 3+ 36 . Moreover, the values of D Al 3+ are in good agreement with values presented here.…”
Section: Resultsmentioning
confidence: 99%
“…[ 105 ] Recently, the detailed Mg 2+ storage mechanism of α ‐MoO 3 in aqueous electrolyte was unveiled by Zhao et al. [ 106 ] In the 2 M MgSO 4 solution, in the first CV cycle, α ‐MoO 3 cathode exhibited two cathodic faradic peaks ( Figure a). The occurrence of two peaks marked a hybrid mechanism for the storage process MoO 3 underwent: an insertion type step (Equation 4) at ‐0.2 V and a conversation type step (Equation 5) at ‐0.7 V. [ 107 ] While the absence of conversation peaks in subsequent cycles suggested that Mg 2+ is stored reversibly through the insertion mechanism.…”
Section: Layered Metal Oxide Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 106 ] Copyright 2022, Wiley‐VCH. a) CV curves at 20 mV s −1 , b) CV curves recorded at various rates, c) GCD profiles at C‐rates of 0.5 C and 5.0 C. The nanosizing strategy.…”
Section: Layered Metal Oxide Materialsmentioning
confidence: 99%